Environmental risk assessment of genetically modified organisms, Volume 3. Methodologies for transgenic fish - Kapuscinski, A. R.; Dana, G.; Dana, G.; Hallerman, E. M.; Hallerman, E. M.; Hayes, K. R.; Hayes, K. R.; Kapuscinski, A. R.; Li, S.; Li, S.; Schei, P. J.; Schei, P. J. (Wallingford :CABI, 2007)
This book on methodologies for risk assessment and management of transgenic fish is written by 44 authors from 19 countries. It is comprised of 10 chapters giving emphasis on developing countries which have transgenic fish research programmes or aquaculture systems that may use transgenic fish in the future. This book is aimed at helping governments, scientists, potential users of genetically modified organisms (GMOs) and civil society organizations in developing countries involved aquaculture and other countries of the world to strengthen their understanding of the scientific knowledge and methods that are available for conducting environmental risk assessments of GMOs.
Keywords: LL240 - Animal Genetics and Breeding, (New March 2000); MM120 - Aquaculture (Animals); WW100 - Genetic Engineering, Gene Transfer and Transgenics, (New June 2002); ZZ900 - Techniques and Methodology